Mobility Method Applied to Calculate the Lubrication Properties of Bearing under Dynamic Loads. (21st January 2013) - He, Tao; Lu, Xiqun; Zhu, Jingzhi
Abstract : The analytical mobility method for dynamically loaded journal bearings was presented, with the intent to include it in a general computational program, such as the dynamic analysis program, that has been developed for the dynamic analysis of general mechanical systems. An illustrative example and numerical results were presented, with the efficiency of the method being discussed in the process of their presentation.